2021
DOI: 10.1007/s40618-021-01612-6
|View full text |Cite
|
Sign up to set email alerts
|

The single-point insulin sensitivity estimator (SPISE) index is a strong predictor of abnormal glucose metabolism in overweight/obese children: a long-term follow-up study

Abstract: Purpose To investigate the relationship between the single-point insulin sensitivity estimator (SPISE) index, an insulin sensitivity indicator validated in adolescents and adults, and metabolic profile in overweight/obese children, and to evaluate whether basal SPISE is predictive of impaired glucose regulation (IGR) development later in life. Methods The SPISE index (= 600 × HDL0.185/Triglycerides0.2 × BMI1.338) was calculated in 909 overweight/obese chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…Among these, the SPISE was developed as an easy and affordable tool for the evaluation of whole-body insulin sensitivity, which is comparable to clamp-derived M-value in sensitivity as well as specificity (19). Several studies have evaluated the SPISE in adult as well as juvenile populations (20,(41)(42)(43)(44)(45)(46). Correa-Burrows et al assessed SPISE for its validity in diagnosing cardiometabolic risks, namely IR and metabolic syndrome, in post-pubertal Hispanic adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, the SPISE was developed as an easy and affordable tool for the evaluation of whole-body insulin sensitivity, which is comparable to clamp-derived M-value in sensitivity as well as specificity (19). Several studies have evaluated the SPISE in adult as well as juvenile populations (20,(41)(42)(43)(44)(45)(46). Correa-Burrows et al assessed SPISE for its validity in diagnosing cardiometabolic risks, namely IR and metabolic syndrome, in post-pubertal Hispanic adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…SPISE was found to be accurate for the prediction of IR in both groups, obese were assessed longitudinally for on average of 6.5 years (range 3.5-10). At follow-up, lower basal SPISE strongly predicted the development of abnormal glucose metabolism (AUROC curve: 0.83 [0.72-0.94] regardless of age, sex, fasting/120 mins glucose and insulin at baseline (46). Of interest, SPISE-IR (=10/SPISE) was also a predictor of coronary heart disease and type 2 diabetes in a group of elderly Swedish men (44).…”
Section: Discussionmentioning
confidence: 99%
“…14) Furthermore, a recent large-scale longitudinal study from Italy confirmed the superiority of the SPISE index for predicting the development of blood glucose abnormalities among overweight/obese children compared with other insulin resistance indices. 14) This research is meaningful since it is the first to examine the clinical utility of the SPISE index in Korean children and adolescents with type 2 diabetes. In this work, the authors suggested that a low SPISE index (<4.49) was an independent factor of type 2 diabetes mellitus in overweight/obese children, after adjusting for well-known risk factors including family history, fatty liver, and/or obesity.…”
mentioning
confidence: 99%
“…"Single point insulin sensitivity estimator for predicting type 2 diabetes mellitus in obese adolescents" by Ha et al [ 13 ] investigated the usefulness of this recently proposed insulin sensitivity marker, the single point insulin sensitivity estimator (SPISE) index, for detecting blood glucose abnormalities or diabetes mellitus in Korean children with obesity. The SPISE index is a lipid- and body mass index-based index of insulin sensitivity that can predict metabolic syndrome in adolescents and adults with more accuracy than other lipid and fasting insulin-based indicators [ 14 ]. Furthermore, a recent large-scale longitudinal study from Italy confirmed the superiority of the SPISE index for predicting the development of blood glucose abnormalities among overweight/obese children compared with other insulin resistance indices [ 14 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation